"Is it because I'm gormless?" A commentary on "Narrative therapy in a learning disability context: a review". Issue 3 (6th July 2015) - Olsen, Angela
Abstract : Purpose: – The purpose of this paper is to reflect on "Narrative therapy in a learning disability context: a review". Design/methodology/approach: – This commentary reflects on the use of Narrative therapy and considers it in the wider context of assisting people with learning disabilities to develop self-understanding. The commentary makes connections between the use of Narrative therapy and narrative approaches to research reporting. Findings: – The use of Narrative therapy can assist in the development of positive personal stories for individuals with learning disabilities. Case study research provides a useful reference point from which to develop future work. Reporting of case studies sometimes omits data that might be useful for others attempting to replicate findings. Originality/value: – This paper highlights the need for authors to ensure that the "small details" are included in research reporting. A narrative approach, rich in detail of research participants might enable authors to tell a "thicker" story, thus improving generalisability.